2022
DOI: 10.52711/0974-360x.2022.00077
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide Nanoparticles Bacterial Synthesis and Application

Abstract: Attributed to their unique properties zinc oxide nanoparticles (ZnONPs) in recent years, have received considerable attention. Notably, research has demonstrated that zinc in living organisms is an essential nutrient. For example, both eukaryotes and prokaryotes including fungi, bacteria, and yeast by using protein, enzyme or microbial cells and other biomolecules compounds are exploited for the synthesis of ZnONPs in either an extracellular or intracellular route. However, the properties of nanoparticles (NPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Additionally, prevents beverage degradation and promotes emulsion preservation [113]. The global citric acid market is projected to reach USD 9 billion by 2030, growing at a Compound Annual Growth Rate (CAGR) of 5.90% for the anticipated period from 2023-2030, according to all available industry data and the development of contemporary industries in agriculture, food, and pharmaceuticals [114]. The expansion of food additives in the processed food industry has a direct impact on the CA market.…”
Section: Citric Acid Global Marketmentioning
confidence: 99%
“…Additionally, prevents beverage degradation and promotes emulsion preservation [113]. The global citric acid market is projected to reach USD 9 billion by 2030, growing at a Compound Annual Growth Rate (CAGR) of 5.90% for the anticipated period from 2023-2030, according to all available industry data and the development of contemporary industries in agriculture, food, and pharmaceuticals [114]. The expansion of food additives in the processed food industry has a direct impact on the CA market.…”
Section: Citric Acid Global Marketmentioning
confidence: 99%
“…On the M. domestica, green synthesized nanoparticle has been found to exhibit bio insecticidal properties . The experiments showed that ZnO Nps have an exceptionally powerful antimicrobial action at incredibly low gram-negative and gram-positive bacterial concentrations, suggesting a stronger antibacterial than chemically produced ZnO Nps (El-Ghwas et al, 2022). The objective of this research is to investigate the comparative efficacy of botanical extracts A. indica and C. limon, along with their biosynthesized zinc oxide nanoparticles against larvae, pupae and adults of M. domestica.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles are of great interest to many researchers, due to their remarkable thermal conductivity, exceptional chemical stability, high oxidation potential and environmentally safe manufacturing process [20,21]. The ZnO nanoparticles possesses several advantageous attributes, including wide bandgap, non-toxicity, high binding energy and chemical stability at ambient temperature [22]. The fundamental and easily adjustable properties of ZnO nanoparticles permits its application in a wide range of sectors including biomedicines, wastewater treatment and photoelectronic devices [23][24][25].…”
Section: Introductionmentioning
confidence: 99%